Penerapan Model Pembelajaran Kontekstual Dalam Proses Belajar Mengajar Mata Pelajaran Sosiologi Kelas X SMK - Susanti, Aguster Jumita (UNIVERSITAS TANJUNGPURA, 2014)
This study aims to improve and develop the skills think students in the learning process teaches sociology at the class X SMK Panca Bhakti Sungai Raya Kubu Raya district. The method used is descriptive research with the intention to describe the actual state of the application model of contextual learning in the teaching-learning process has been implemented by teachers Panca Bhakti sociology SMK Sungai Raya. Results of data analysis showed that teachers are already implementing measures of contextual learning, contextual learning components and capable teachers assist students in connecting the subject matter, the teacher is able to manage the class well, teachers can carry out group discussions in class and the ability of teachers in conditioning himself as a teacher who is respected by his students and will accept responses wisely as well as questions submitted from students to teachers.Keywords : Application, Contextual Learning, Sociology Lesson.Â